2009
DOI: 10.1073/pnas.0907652106
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease-like pathological features in transgenic mice expressing the APP intracellular domain

Abstract: The hypothesis that amyloid-␤ (A␤) peptides are the primary cause of Alzheimer's disease (AD) remains the best supported theory of AD pathogenesis. Yet, many observations are inconsistent with the hypothesis. A␤ peptides are generated when amyloid precursor protein (APP) is cleaved by presenilins, a process that also produces APP intracellular domain (AICD). We previously generated AICDoverexpressing transgenic mice that showed abnormal activation of GSK-3␤, a pathological feature of AD. We now report that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
227
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(239 citation statements)
references
References 36 publications
9
227
0
3
Order By: Relevance
“…45 We previously demonstrated that Tip60 HAT action is critical for nervous system development and cognitive processes such as synaptic plasticity, axonal outgrowth and transport via its transcriptional regulation of genes enriched for a variety of specific neuronal processes. 40 Consistent with a role for Tip60 in nervous system function, our laboratory 7,17,30,34,[40][41][42][43][44]46 and others 7,30,[47][48][49][50] have shown that the HAT Tip60 is implicated in Alzheimer's disease (AD) based on its role in epigenetic neuronal gene control via its formation of a transcriptionally active complex with the processed C-terminal amyloid precursor protein (APP) intracellular domain (AICD). 30,43,47,48,[51][52][53][54][55][56][57] Loss of Tip60 HAT activity and/or improper recruitment of this complex to specific gene promoters causes epigenetic misregulation of a variety of genes causatively associated with neurodegeneratation.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…45 We previously demonstrated that Tip60 HAT action is critical for nervous system development and cognitive processes such as synaptic plasticity, axonal outgrowth and transport via its transcriptional regulation of genes enriched for a variety of specific neuronal processes. 40 Consistent with a role for Tip60 in nervous system function, our laboratory 7,17,30,34,[40][41][42][43][44]46 and others 7,30,[47][48][49][50] have shown that the HAT Tip60 is implicated in Alzheimer's disease (AD) based on its role in epigenetic neuronal gene control via its formation of a transcriptionally active complex with the processed C-terminal amyloid precursor protein (APP) intracellular domain (AICD). 30,43,47,48,[51][52][53][54][55][56][57] Loss of Tip60 HAT activity and/or improper recruitment of this complex to specific gene promoters causes epigenetic misregulation of a variety of genes causatively associated with neurodegeneratation.…”
mentioning
confidence: 88%
“…30,43,47,48,[51][52][53][54][55][56][57] Loss of Tip60 HAT activity and/or improper recruitment of this complex to specific gene promoters causes epigenetic misregulation of a variety of genes causatively associated with neurodegeneratation. 30,43,47,50,51 During the past several years, my laboratory has published a compendium of studies characterizing a functional interaction between Tip60 and the APP-C terminus (AICD) in mediating multiple cognitive neuronal processes using Tip60; APP transgenic Drosophila we generated as a robust model system. 7,17,30,34,[40][41][42][43] To develop this system, we utilized well characterized APP Drosophila lines that express equivalent and moderate levels of either GAL 4 responsive full length human APP (hAPP695) or APP lacking the AICD domain (APP-dCT) 43,58,59 and adapted them to harbor our GAL4 responsive Drosophila Tip60 wild-type (Tip60 WT ) or dominant negative HAT mutant (Tip60 E431Q ) transgenes.…”
mentioning
confidence: 99%
“…Au-delà du rôle de l'APP comme précurseur de peptides intervenant dans la MA, APP a une action physiologique neurotrophique et synaptogénique, soit comme protéine transmembranaire, soit par les fragments de clivage (CTF, C-terminal fragment et APPs) (Figure 1) [9,10]. Ces fragments de clivage ont encore été très peu étudiés, même si le fragment CTF semble avoir lui-même un rôle pathologique [11]. Le lien étant établi entre niveaux de peptides -amyloïdes et déclin cognitif, la question se pose des mécanismes par lesquels les oligomè-res A solubles affectent la mémoire.…”
Section: Peptide Amyloïde Et Synapsesunclassified
“…1 The surprise is that the mice develop the disease phenotype independently of β-amyloid, the extracellular fragment of amyloid-β (A4) precursor protein that many believe to be the prime suspect in Alzheimer's disease.Instead, the disease in these mice appears to be caused by an intracellular fragment of amyloid-β (A4) precursor protein (APP) that goes on to trigger both abnormal hyperphosphorylated microtubule-associated protein-τ (MAPT; FTDP-17; tau) phosphorylation and neuronal death-two hallmarks of human AD that are not seen in the most widely used mouse models.The model thus raises fresh doubts about whether β-amyloid (Aβ) is really the cause of pathology and instead points to the intracellular portion of APP as the real culprit in AD.Aβ is a byproduct of proteolytic processing of APP that accumulates on the outside of cells in amyloid plaques. Aβ is toxic to neurons and is often detected in the serum and brains of AD patients.…”
mentioning
confidence: 99%
“…1 The surprise is that the mice develop the disease phenotype independently of β-amyloid, the extracellular fragment of amyloid-β (A4) precursor protein that many believe to be the prime suspect in Alzheimer's disease.…”
mentioning
confidence: 99%